Experimental and numerical investigation of Long Glass Fiber Reinforced Polypropylene composite and application in automobile components - Duan, Shuyong; Yang, Xujing; Tao, Yourui; Mo, Fuhao; Xiao, Zhi; Wei, Kai (Transport, 2018)
Due to the good mechanical performances and design flexibility of Long Glass Fiber Reinforced Polypropyl-ene (LGFRP) composite, it has been increasingly used in the automotive components, in which the LGFRP components are likely to sustain different strain rates loading during a crash event. This study aims to investigate the correlations between the LGFRP and strain rate, which will be applied to crash-worthiness and energy absorbing property analysis of a bumper beam under the longitudinal impact. Firstly, strain rate dependent material properties are determined, for which the experimental procedure is explained in detail on the tensile specimens of long glass fiber and polypropylene matrix based composite configurations. The gained experimental results provide the input parameters for a numerical analysis of specimens. The numerical results of properties are compared with those from tests. The constitutive model that fits for LGFRP is employed to crash-worthiness and energy absorbing property analysis of a bumper beam under the longitudinal impact.First Published Online: 17 May 2017